Pengaruh Suplementasi Probiotik A3-51 terhadap Derajat Imunitas Oreochromis niloticus Didasarkan pada Angka Kuman pada Ginjal Setelah Uji Tantang dengan Aeromonas hydrophila dan Aeromonas salmonicida achromogenes - Agus Irianto; Hernayanti Hernayanti; Ning Iriyanti (Jurnal Perikanan Universitas Gadjah Mada, 2006)
Objectives of this research was to know the effect of probiotic A3-51 supplementation on food to the total number of bacteria in kidney and mortality of Oreochromis niloticus after challenge test with Aeromonas hydrophila and Aeromonas salmonicida achromogenes. This research was consisted of two experiment, the first was to know the highest immunity level of fish based on the number of macrophage and its phagocytic activity. Meanwhile, the second was to know the immunity level of fish challenged with A. hydrophila and A. salmonicida achromogenes by intra-peritoneal injection. The experiment used Completely Randomized Design in triplicates. The result from the first experiment showed that the highest non spesific immune system response, by means number of macrophage, was found 21 days treatment. The second experiment showed that the highest total number of bacteria in kidney and mortality level were 20.23 x 108 cells/g and 46.67%, respectively, both was found in control fish injected intra-peritoneally with A. salmonicida achromogenes.